Maxillary sinusitis and fungal infection - Hassan, M; Khan, MH; Ahmed, AU; Morshed, MM; Chakraborty, MR; Ahmed, K (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Jul;20(3):459-462 The abstract of this article is available on the PubMed website